Static Characteristics of the Anaerobic Digestion of Organic Wastes with Production of Hydrogen and Methane, Including Substrate Inhibition Influence - Elena Chorukova; Lyudmila Kabaivanova (International Journal Bioautomation)
In this paper, static characteristics of a simple mathematical model of a two-stage anaerobic digestion (AD) process for sequential production of hydrogen (Н2) and methane (СН4) are derived. The influence of substrate inhibition in the first and second bioreactors is considered. Different process variables are described in the considered mathematical model. The concentration of the influent organic matter is assumed to be the main external disturbance reflected in the model. The obtained input-output static characteristics for the energy carriers (H2 and CH4) could be used to control and optimize the subjected process.